(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
This study intends to analyze the changes in coastal vegetation cover of recent times and to explore effective ways of integrating local communities in coastal forest management program for the future sustainability of coastal forestry. Changes in coastal forestry have been identified through the NDVI operation using satellite images from 1991-2021. Results show that a total of 4105.3 km2 of coastal vegetation cover decreased at a rate of 0.342% per year in the last 30 years where afforested lands are being converted to various land uses. This loss is mainly due to the rapid expansion of human settlements and agricultural activities. Focus group discussions and key informant interviews were conducted to collect primary data about the integration of the community in the central coastal areas of Sandwip, Nijhum Dwip, and Char Kukri Mukri. Study findings reveal poor participation of local people in coastal forest management practices and identified several challenges as the main hindrance to integration. Finally, the study developed a framework for better forest management practices useful to protect afforested areas, especially in the central coastal area of Bangladesh. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11 (2): 2022, P 15-31